The Efficacy of Heat Acclimatization Pre-World Cup in Female Soccer Players - Meylan, César M. P.; Bowman, Kimberly; Stellingwerff, Trent; Pethick, Wendy A.; Trewin, Joshua; Koehle, Michael S. (Frontiers in Sports and Active Living, 2021)
The efficacy of a 14-day field-based heat acclimatization (HA) training camp in 16 international female soccer players was investigated over three phases: phase 1: 8 days moderate HA (22. 1°C); phase 2: 6 days high HA (34.5°C); and phase 3: 11 days of post-HA (18.2°C), with heart rate (HR), training load, core temp (Tc), and perceptual ratings recorded throughout. The changes from baseline (day−16) in (i) plasma volume (PV), (ii) HR during a submaximal running test (HRex) and HR recovery (HRR), and (iii) pre-to-post phase 2 (days 8–13) in a 4v4 small-sided soccer game (4V4SSG) performance were assessed. Due to high variability, PV non-significantly increased by 7.4% ± 3.6% [standardized effect (SE) = 0.63; p = 0.130] from the start of phase 1 to the end of phase 2. Resting Tc dropped significantly [p < 0.001 by −0.47 ± 0.29°C (SE = −2.45)], from day 1 to day 14. Submaximal running HRR increased over phase 2 (HRR; SE = 0.53) after having decreased significantly from baseline (p = 0.03). While not significant (p > 0.05), the greatest HR improvements from baseline were delayed, occurring 11 days into phase 3 (HRex, SE = −0.42; HRR, SE = 0.37). The 4v4SSG revealed a moderate reduction in HRex (SE = −0.32; p = 0.007) and a large increase in HRR (SE = 1.27; p < 0.001) from pre-to-post phase 2. Field-based HA can induce physiological changes beneficial to soccer performance in temperate and hot conditions in elite females, and the submaximal running test appears to show HRex responses induced by HA up to 2 weeks following heat exposure.